Germplasm characterization, diversity study and genome-wide association in coffea canephora - Zaidan, Iasmine Ramos (2022)
The germplasm remaining from ancient seminal crops of Conilon (Coffea canephora) in the south of Espírito Santo must be characterized and preserved as they are potential sources of genetic variability and resources for genetic breeding programs. With the release of commercial clones and the use of generally few clonal materials, there may be a narrowing of the genetic base. The aim of this study were (i) to characterize and investigate the genetic diversity of 388 half-sib families of new and promising genotypes of C. canephora from old seminal crops in the south of Espírito Santo, based on morpho agronomic traits; (ii) to evaluate the genetic diversity and population structure of 280 genotypes and 29 commercial clones cultivated in the state by high throughput genotyping SNP data; (iii) to identify chromosomal regions with significant associations with eight phenotypic traits by GWAS. The experiment was installed in April 2018 in Mimoso do Sul - ES in Federer augmented blocks with five commercial clones used as controls. Each of 388 half-sib families had five plants, totaling 2,085 plants. The characteristics evaluated were plant height, stem diameter, average height growth rate, average diameter growth rate, rust incidence, leaf miner infestation, mealybug infestation, drought tolerance. Biotic and abiotic stresses were assessed by visual analysis using a rating scale. Cluster analyzes were performed for the data referring to the average growth rates that were subjected to linear regression and the values of the regression constants and regression coefficients were used in the construction of the dendrogram, a second cluster was made to all data referring to the latest measurements and Pearson's correlation analysis was done to detect the correlation between the traits. A total of 251 genotypes selected in the experimental field, including commercial clones, and 29 genotypes from Incaper were high-throughput genotyping using the DArTseq methodology. SNP were filtering by quality parameters and the data were used for genetic diversity, population structure and molecular analysis of variance. The GWAS study includes 251 genotypes and eight traits. For the phenotypic data, mixed models were used, and, from the sum of the genetic values and the residues of the genotyped materials, the p-values were calculated. The SNP markers with significant associations (p < 0.05) along the 11 chromosomes of C. canephora had the putative function of the genes verified. In the 1 morpho-agronomic characterization, eight divergent groups and in the second analysis nine groups detected, shows the germplasm variation. Positive correlations were detected among plant height, stem diameter, average height growth rate and average diameter growth rate. Negative correlations for all stresses with the characters of vegetative development indicated that such adverse conditions impaired the initial development of the coffee plant. A total of 2,542 filtered SNPs revealed six groups by cluster analysis and two genetic groups by STRUCTURE. The high frequency of heterozygotes (He) for some of the groups formed by the cluster analysis indicates the genetic diversity. High FST values were detected between groups 4 and 2 (0.60), 2 and 5 (0.60), 4 and 3 (0.50) and between the two genetic groups (0.59). In the GWAS analysis, 115 SNPs showed significant associations with seven traits: 48 for height growth rate; 20 for mealybug incidence; seven for plant height and diameter growth rate; 11 for stem diameter; 16 for incidence of rust and five for incidence of leaf mining. Most of these SNPs are located within or close to candidate genes. The putative function of these candidate genes GSCOC_T00019303001, GSCOC_T00022693001, GSCOC_T00039643001 and GSCOC_T00040251001 are related to plant defense mechanisms to protect against pathogens, pests and abiotic stresses. Other candidate genes such as GSCOC_T00040077001, GSCOC_T00028217001 and GSCOC_T00021883001 presented putative functions related to plant development and plant hormones. All the results show the importance of preserving old crops in the south of Espírito Santo as a source of genetic resources for coffee breeding programs. The phenotypic and genetic diversity detected demonstrate that the old seminal crops in the south of the state constitute a very rich germplasm bank. This valuable source must be maintained and conserved to guarantee the sustainability of the coffee crop to expand the genetic base that was reduced with the replacement of clonal cultivars. In addition, chromosomal regions detected associated with important traits can be used in studies of selection assisted by molecular markers to select plants of favorable attributes for the genetic breeding of coffee.